Struvite Precipitation from Centrate—Identifying the Best Balance Between Effectiveness and Resource Efficiency - Andreas Kolb; Tim Gebhardt; Thomas Dockhorn (Resources)
In the context of struvite precipitation, the most significant gap pertains to the transfer of knowledge from scientific research to practical applications. The primary objective of this study is twofold: firstly, to identify the most critical process parameters influencing struvite precipitation and, secondly, to translate these parameters into a pragmatic tool for real-world applications. This study investigates the precipitation of struvite from digestion centrate to obtain information on the appropriate precipitation conditions for different initial chemical compositions. We carried out 24 lab-scale experiments to investigate the effect of varying pH value (7.0–8.5), temperature (5 °C and 33 °C) and initial phosphate concentrations (353; 165; 68 mg/L) on struvite precipitation. Varying the pH had the strongest influence on precipitation efficiencies. Adjusting pH from 7 to 8.5 increased PO4-P removal from 1.4% to 98.8%, whereas temperature had little impact on PO4-P removal. Furthermore, we found that a saturation index of at least 1.7 is imperative to precipitate at least 90% of the available PO4-P. Based on the results, we developed a nomogram showing the resulting saturation index and the associated PO4-P removal efficiency for variable initial PO4-P and pH levels. The tool developed in this study enables users to directly identify the so-called ‘sweet spot’, which is the optimal balance between process effectiveness and resource efficiency, for each centrate.